2019
DOI: 10.18203/2349-3291.ijcp20193722
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological study of dengue fever in Ajmer region

Abstract: Background: Dengue infection is a major challenge to public health, especially in South-East Asia. It present with a diverse clinical spectrum. Estimates suggest that annually over 50 million cases of dengue hemorrhagic fever (DHF) occur in Asian countries with a case fatality rate of less than 5%. Of those with DHF, at least 90% are children younger than 15 years old. In humans, dengue infection causes a spectrum of illness ranging from relatively mild, non-specific viral syndrome known as Dengue fever (DF) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…A study from North India showed similar observation of most cases of dengue from the age group of 0 to 15 years. 13 Dengue epidemic between 1990 and 2006 from Delhi, Tamil Nadu, Madhya Pradesh, Pondicherry, and Uttar Pradesh (2003)(2004)(2005)(2006) found most cases in the 5-12-year age group. 14,15 The lack of immunity among children could be the possible role of the high fatality rate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A study from North India showed similar observation of most cases of dengue from the age group of 0 to 15 years. 13 Dengue epidemic between 1990 and 2006 from Delhi, Tamil Nadu, Madhya Pradesh, Pondicherry, and Uttar Pradesh (2003)(2004)(2005)(2006) found most cases in the 5-12-year age group. 14,15 The lack of immunity among children could be the possible role of the high fatality rate.…”
Section: Resultsmentioning
confidence: 99%
“…7 Fever, myalgia, and thrombocytopenia were the most common clinical features reported by patients with dengue infection in our study and most studies from country. 11,13,25,26 DF was reported in 53.02% of patients, DHS in 40.49%, and DSS in 6.40% of patients infected with DENV. Almost similar findings were reported from Ajmer region in 2019.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations